Diagnostics of Inherited Bleeding Disorders of Secondary Hemostasis: An Easy Guide for Routine Clinical Laboratories - Lippi, Giuseppe; Franchini, Massimo; Favaloro, Emmanuel J. (Seminars in Thrombosis and Hemostasis, 2016)
The investigation of inherited bleeding disorders of secondary hemostasis remains a challenge for most clinical laboratories, especially those that lack experience or specialized personnel. Bleeding can be essentially caused by a variety of acquired or congenital conditions, which impair either primary or secondary hemostasis. Since a universally agreed approach for the diagnostics of hemorrhagic disorders is still unavailable, this article aims to provide an easy guidance for routine clinical laboratories. This pragmatic approach to identifying and diagnosing inherited bleeding disorders of secondary hemostasis entails a multifaceted strategy, based on a collection of personal and family history, the results of first-line tests, which can then be followed by second- or third-line analyses to definitely establish the specific nature and the severity of the bleeding phenotype. Briefly, the presence of profound hemorrhages rather than mucocutaneous bleeding is suggestive of a disorder of secondary hemostasis. Although a positive family history is frequently reported in patients with congenital conditions, the lack of clinically meaningful symptoms in patient's relatives is not absolutely indicative of an acquired disorder. The next step encompasses the assessment of first-line coagulation tests (i.e., prothrombin time, activated partial thromboplastin time, and fibrinogen) if family history is not suggestive of a specific factor deficiency. The emergence of abnormal data of these assays and the variable combination of their results is then helpful to guide the performance of second-line tests, in particular specific factor assays, which will then provide a reasonable basis for a preliminary diagnosis. Third-line tests (namely, immunological assays of clotting factors and molecular biology) are then supportive for a final diagnosis and for identifying the nature of the factor deficiency (i.e., quantitative or functional).
Keywords: bleeding disorders; secondary hemostasis; diagnosis; coagulation; laboratory testing; factor deficiencies